2016
DOI: 10.1007/s13361-016-1481-2
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Reactions of Ions Derived from Anionic Uranyl Formate and Uranyl Acetate Complexes

Abstract: Abstract. The speciation and reactivity of uranium are topics of sustained interest because of their importance to the development of nuclear fuel processing methods, and a more complete understanding of the factors that govern the mobility and fate of the element in the environment. Tandem mass spectrometry can be used to examine the intrinsic reactivity (i.e., free from influence of solvent and other condensed phase effects) of a wide range of metal ion complexes in a species-specific fashion. Here, electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 41 publications
8
36
2
Order By: Relevance
“…In another set of experiments that are relevant to the present study, electrospray ionization (ESI) and multiple‐stage (MS n ) tandem mass spectrometry were used to create and characterize ions derived from anionic UO 2 2+ ‐formate and ‐acetate precursors . When the levels of background H 2 O are low, [UO 2 (O 2 C─H) 3 ] − fragments by decarboxylation and elimination of CH 2 ═O, ultimately to produce the oxo‐hydride [UO 2 (O)(H)] − .…”
Section: Introductioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In another set of experiments that are relevant to the present study, electrospray ionization (ESI) and multiple‐stage (MS n ) tandem mass spectrometry were used to create and characterize ions derived from anionic UO 2 2+ ‐formate and ‐acetate precursors . When the levels of background H 2 O are low, [UO 2 (O 2 C─H) 3 ] − fragments by decarboxylation and elimination of CH 2 ═O, ultimately to produce the oxo‐hydride [UO 2 (O)(H)] − .…”
Section: Introductioncontrasting
confidence: 97%
“…The low level of background H 2 O in the LIT also allowed us to revise the intrinsic dissociation pathways for a range of species such as [UO 2 (NO 3 )] + , [UO 2 (ClO 4 )] + , and [UO 2 (O 2 C‐CH 3 ) 3 ] − . For example, with relatively high levels of background H 2 O, CID of [UO 2 (NO 3 )] + generated peaks corresponding to [UO 2 (H 2 O)] + and UO 2 + .…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…CID of [U VI O 2 (ClO 4 )(H 2 O)] + (MS 4 stage, Figure C), created [U VI O 2 (ClO 4 )] + ( m/z 369) by loss of the final H 2 O ligand, and all of the fragmentation reactions to this point were in general agreement with the earlier study that used a 3D ion trap . One notable difference, however, was that the number and relative abundance of H 2 O was significantly lower in the present experiments, consistent with several recent studies by our group …”
Section: Resultssupporting
confidence: 92%
“…We have recently demonstrated that dissociation pathways and reactions are revealed in experiments that use a 2D linear ion trap (LIT) that were not observed in prior studies that employed 3D ion traps. For example, in a recent investigation of the MS n CID of U VI O 2 2+ /acn complexes, use of the LIT (with the associated lower levels of background H 2 O) allowed us to sequentially eliminate acn ligands to leave the bare U VI O 2 2+ cation, as well as generate NU VI O + by CID of [U VI O 2 (CN)] + .…”
Section: Introductionmentioning
confidence: 99%